Analysis Influence Go-Food Plus Member Promotion and Service Quality on User Loyalty in the Go-Jek Application - Lestari, Mentari Puji; Andara, Melisa Dwi; Wadhwa, Sunny (Prosiding International conference on Information Technology and Business (ICITB), 2023)
The aim of this research is to analyze the influence of promotions, service quality and user loyalty on the Go-Jek application. Mediating variables and to find out the most dominant variables on promotion, service quality and user loyalty on the Go-Jek application. The analytical method in this research uses quantitative methods, descriptive analysis methods . The test stage carried out was a data analysis test in this research using a linear regression analysis test , t test, f test. The data used in this research used a questionnaire instrument and valid data was collected from 100 respondents. The sampling method in this research is a purposive sampling technique. The research results show that the variables of promotion, service quality and user loyalty have a positive and significant influence on the consumer variables of Go-Jek application users.Â Keywords: Promotion, Service Quality, User Loyalty